De política pública à ideologia de gênero: O processo de (des)institucionalizaç\~ao das políticas para as mulheres de 2003 a 2020 - Carolina Pereira Tokarski; Krislane de Andrade Matias; Luana Sim\~oes Pinheiro; Ranna Mirthes Sousa Correa (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This article aims to evaluate to what extent the process of dismantling policies for women has been installed in federal public management and the intensity with which it is effective over the last few years. To this end, we followed the trajectory of advances and setbacks that marked this field between the period from 2003 to 2020, dividing it into three phases: i) 2003-2014: the consolidation of a policy agenda for women; ii) 2015-2018: the stagnation of this agenda; and iii) 2019-2020: the delegitimization of the agenda and dismantling of policies. The focus consists on analyzing the capacity of the institutional mechanisms for the advancement of women to manage gender mainstreaming and to implement actions under their responsibility. The indicators raised allow us to conclude that there was, throughout the period analyzed, a deinstitutionalization of the gender perspective in the governmental structure that begins with a process of reduction, paralysis and ineffectiveness of the main instruments of public policies for women, which is followed by a dismantling of this agenda within the State, by the dismissal of the principle of gender equality and by the transversality of a conservative family agenda.
10419/284922
Keywords: 330; public policies for women; institucionalization of gender agenda; dismantling public policies; family mainstreaming; gender mainstreaming; Institutional Mechanism for the Advancement of Women